Aggregation‐Induced Improvement of Catalytic Activity by Inner‐Aggregate Electronic Communication of Metal‐Fullerene‐Based Surfactants. Issue 10 (6th April 2020) - Kunkel, Marius; Bitter, Stefan; Sailer, Frank; Winter, Rainer F.; Polarz, Sebastian
Abstract: A paradigm for active constituents in (homogeneous) catalysis is that optimum performance requires maximum dispersion. Generally, aggregation results in a decline. This is a different case in supramolecular catalysis. A new concept based on surfactants equipped with functional heads is presented, which becomes a more active catalyst itself upon aggregation. The head group of the surfactants is composed of a diethylenetriamine‐functionalized fullerene capable of coordinating to catalytically active metals like Co II . The improvement of catalytic properties upon aggregation is demonstrated via electrocatalytic water‐splitting reaction as a model system. Detailed electrochemistry studies were performed at concentrations below and above the critical aggregation concentration ( cac ). While isolated surfactant molecules represent only moderately active catalysts, drastic improvement of efficiency in the hydrogen evolution (HER) as well as in the oxygen evolution reactions (OER) were detected, once vesicular structures have formed. Self‐organization of the surfactants leads to an increase in turnover frequencies of up to 1300 % (HER). The strongly beneficial effect of aggregation arises from the favorable alignment of individual molecules, thus, facilitating intermolecular charge transfer processes in the vesicles. Abstract : Supramolecular catalysis gives way to new catalytic systems. Here, a prototype system of a fullerene based catalyst is presented that changes the catalyst's properties upon aggregation. This effect was evaluated with electrocatalytic water splitting reaction as a test reaction. The catalytic activity is enhanced due to aggregation induced inter‐molecular electronic communication.